Optimalisasi Digital Marketing Melalui Live Streaming Tiktok dalam Meningkatkan Brand Awareness pada Dasilva Batik - Listyo Ferdi Suhendar; Umi Khabibah; Tri Ramadani Arjo (Indo Publishing, 2026)
The development of digital marketing has encouraged businesses to utilize social media, including TikTok live streaming, as a marketing strategy. However, Dasilva Batik Malang has not been able to utilize this feature optimally due to an average audience watch duration of only 10 seconds, indicating weak brand awareness, inconsistent broadcasting schedules and streaming times, short broadcast durations, less interactive product presentations by the host and low audience engagement, which have resulted in weak brand awareness. This study aims to identify the implementation of TikTok live streaming optimization and analyze its effectiveness in increasing the brand awareness of Dasilva Batik Malang. This study employed an action research method using the Kemmis and Taggart cycle approach. Data were collected through observation, interviews, documentation, and questionnaires distributed to 8 respondents. The data were analyzed using the AIDA model and a Likert scale through total score calculation (Total Score = Frequency × Weight), simple tabulation (X = fi/Σfi × 100%), mean score calculation (X = Σfi.wi/Σfi), and engagement rate analysis (Engagement Rate = Likes + Comments + Shares + Gift/Total Views × 100%). The questionnaire results showed that none of the respondents selected disagree or strongly disagree for any of the 12 statements. Meanwhile, the AIDA analysis showed an overall mean score of 4.03, categorized as very good. The action dimension achieved the highest score (4.17), followed by attention (4.12), interest (4.04), and desire (3.79). The engagement rate from the two best live streaming sessions averaged 6,20%, which is categorized as high, with the first sessions reaching 7,40% and the second session 5%. The results indicate that optimizing TikTok live streaming is effective in increasing the brand awareness of Dasilva Batik Malang. The implementation of this strategy successfully increased the audience’s brand awareness from the unaware of brand stage to the brand recognition stage. Therefore, Dasilva Batik is recommended to maintain consistency in live streaming activities and strengthen the desire dimension through promotional offers during live streaming sessions to further enhance brand awareness and increase consumers’ interest in the products.